1995
DOI: 10.1093/jac/35.5.577
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of Leishmania species to aminosidine

Abstract: The aminoglycoside, aminosidine exhibited ED50S of between 1 and 5 microM against the amastigotes of Leishmania major and Leishmania tropica in mouse peritoneal macrophages whereas other strains causing New World cutaneous leishmaniasis such as Leishmania braziliensis were more refractory. Aminosidine was also active against all but one of the Leishmania donovani strains tested and when combined with sodium stibogluconate, the drug showed marked potentiation against the amastigotes of L. donovani in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 0 publications
4
49
0
3
Order By: Relevance
“…One explanation for this phenomenon is the intrinsic difference in species sensitivity to these drugs. In general, studies using the amastigote-macrophage model, L. donovani and L. brasiliensis were found to be three-to fivefold more sensitive to sodium stibogluconate than L. major, L. tropica, and L. mexicana (5,13,111). This was also shown in earlier studies by Berman et al, using another amastigotemacrophage model, which also demonstrated a wide variation in the sensitivity of isolates from cutaneous leishmaniasis cases to pentavalent antimonials (15).…”
Section: Antimonialssupporting
confidence: 63%
“…One explanation for this phenomenon is the intrinsic difference in species sensitivity to these drugs. In general, studies using the amastigote-macrophage model, L. donovani and L. brasiliensis were found to be three-to fivefold more sensitive to sodium stibogluconate than L. major, L. tropica, and L. mexicana (5,13,111). This was also shown in earlier studies by Berman et al, using another amastigotemacrophage model, which also demonstrated a wide variation in the sensitivity of isolates from cutaneous leishmaniasis cases to pentavalent antimonials (15).…”
Section: Antimonialssupporting
confidence: 63%
“…Paromomycin is poorly absorbed after oral dosing and is still marketed as an oral treatment for amoebiasis and giardiasis and to decrease bacterial load in the gut in hepatic coma (Humatin; Parke-Davis, Morris Plains, NJ, USA). The antileishmanial properties of paromomycin were recognised by Kellina (1961) and were confirmed by Neal et al (1968;1995). Two 'proof of concept' studies, by the Kenya Fig.…”
Section: Paromomycinmentioning
confidence: 77%
“…The most important study is done by Sundar and Olliaro (2007), which led to the licensing of paromomycin for VL in India. Neal et al (1995) showed paromomycin and SSG to be synergistic in vitro and additive in a mouse model of VL. In a study of interactions between anti-leishmanial drugs, Seifert and Croft (2006) reported miltefosine and paromomycin to be additive in vitro and synergistic in the mouse VL model.…”
Section: Paromomycinmentioning
confidence: 96%
See 2 more Smart Citations